Integrating Artificial Intelligence Technique and Lexicon of Verbs in Automated Database Design Diagnosing - Mohd Noah, Shahrul Azman; D. Williams, Michael (Malaysian Journal of Computer Science, 2017)
Conceptual database design is seen as the most important stage of a database design process, as the conceptual model produced at this stage is the first design model constructed with formal and detailed semantics. The stage, however, is also viewed as a difficult task for designers, and the potential for committing and correcting errors is significant. As a result, it is not surprising to see the emergence of a number of automated systems employing artificial intelligence (AI) techniques in providing assistance in the design of such a model. This paper presents one such tool, called the Intelligent Object Analyser (IOA). Although the tool exhibited the capacity of performing two aspects of design (design synthesis and design diagnosis), its major contribution is to assist users within the scope of design diagnosis from its capability to detect errors, and suggest corrections in design. Apart from incorporating the AI techniques, the tool also integrates a domain specific lexicon of verbs, which is meant to enhance the tool’s diagnostic capabilities. The tool demonstrates the practical integration of AI techniques and domain specific lexicon to the aspects of database design diagnosing. The paper concludes with a discussion of areas for future development in this field.